Effects of shoreline modification on lake littoral macroinvertebrate assemblages - Jurca, Tamara (Trinity College (Dublin, Ireland). Department of Zoology, 2012)
The general aim of this study was to explore the effects of shoreline modifications on the structure of littoral macroinvertebrate assemblages in lakes, across the gradients of nutrients and alkalinity concentrations. Following this general aim, several aspects of the topic were investigated. The first aim was to establish whether shoreline habitat characteristics influence the composition of littoral macroinvertebrate assemblages. For this purpose, characteristics of shoreline habitats were recorded using the Lake Habitat Survey and associated with the assemblages at each site across six studied lakes. The relevance of specific shoreline features in structuring the macroinvertebrate composition was estimated.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin.